L’impolitesse linguistique : vers un nouveau paradigme de recherche ? - Manuel Jobert (Lexis: Journal in English Lexicology)
The aim of this paper is to assess the relevance of the studies on impoliteness carried out in the present context. Although researchers are increasingly trying to analyse impolite utterances, the theoretical frameworks they develop seem to rely heavily on the Brown & Levinson [1978] tradition, albeit in a reverse fashion. This paper particularly focuses on the models put forward by Culpeper [1996] and Bousfield [2008].